OLIF versus MI-TLIF for patients with degenerative lumbar disease: Is one procedure superior to the other? A systematic review and meta-analysis - Wang, Jianqiang; Liu, Jingwei; Hai, Yong; Zhang, Yiqi; Zhou, Lijin (Frontiers in Surgery, 2022)
Purpose To compare the effectiveness and safety of oblique lateral interbody fusion (OLIF) and minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) for degenerative lumbar disease. Methods We searched relevant studies in Embase, PubMed, Cochrane, and Web of Science databases comprehensively from inception to March 2022. The data were extracted from included studies, including operation indications, radiographic parameters, and clinical outcomes. Random or fixed-effects models were used in all meta-analyses according to the between-study heterogeneity. Results In total, 30 studies, including 2,125 patients, were included in this meta-analysis. Our study found similar disk height, length of hospital stay, visual analog scale (VAS), and Oswestry disability index(ODI) between the two groups. However, the OLIF showed an advantage in restoring lumbar lordotic angle compared with MI-TLIF, with the pooled mean change of 17.73° and 2.61°, respectively. Additionally, the operative time and blood loss in the OLIF group appeared to be less compared with the MI-TLIF group. Regarding complications, the rates of the two groups were similar (OLIF 14.0% vs. MI-TLIF 10.0%), but the major complications that occurred in these two procedures differed significantly. Conclusion The results of disk height, length of hospital stay, VAS, and ODI between the OLIF and MI-TLIF groups were similar. And the OLIF was superior in restoring lumbar lordotic angle, operative time, and blood loss. However, the OLIF group's complication rate was higher, although not significantly, than that in the MI-TLIF group.